Quadratic blind linear unmixing: A graphical user interface for tissue characterization. Issue 124 (February 2016) - Gutierrez-Navarro, O.; Campos-Delgado, D.U.; Arce-Santana, E.R.; Jo, Javier A.
Abstract : Highlights: Interactive software which implements blind linear unmixing algorithms in Matlab. Estimation of the number of components, the end-members and their abundances. Estimations based on constrained quadratic optimization and Neyman–Pearson tests. Software freely available in a hosted webpage by one of the developing institutions. Quick, easy-to-use and efficient tool for multi/hyper-spectral data decomposition. Abstract: Spectral unmixing is the process of breaking down data from a sample into its basic components and their abundances. Previous work has been focused on blind unmixing of multi-spectral fluorescence lifetime imaging microscopy (m-FLIM) datasets under a linear mixture model and quadratic approximations. This method provides a fast linear decomposition and can work without a limitation in the maximum number of components or end-members. Hence this work presents an interactive software which implements our blind end-member and abundance extraction (BEAE) and quadratic blind linear unmixing (QBLU) algorithms in Matlab. The options and capabilities of our proposed software are described in detail. When the number of components is known, our software can estimate the constitutive end-members and their abundances. When no prior knowledge is available, the software can provide a completely blind solution to estimate the number of components, the end-members and their abundances. The characterization of three case studies validates the performance of the new software: ex-vivo human coronary arteries, human breast cancer cell samples, and in-vivo hamster oral mucosa. The software is freely available in a hosted webpage by one of the developing institutions, and allows the user a quick, easy-to-use and efficient tool for multi/hyper-spectral data decomposition.